Objectives and Policies of the European Union in the Opinion of its Citizens - a Multivariate Approach - Grześkowiak , Alicja (Studia Oeconomica Posnaniensia, 2018)
The article presents the results of the analyses of the opinions of citizens of EU countries on the key activities and priorities of the community. A comparison of views on the Europe 2020 objectives and policies of the European Union was performed on the basis of the results of surveys carried out in the framework of the Euro barometer. The dispersion and the changes were evaluated by selected statistical measures and data visualization techniques. Due to the multivariate nature of the data, the principal component analysis was used to study the structures of the datasets under consideration. The analyses indicate the existence of significant differences in the perception of the objectives and policies of the EU by citizens of the countries belonging to the European Community.